A metal-organic framework material separation membrane, its preparation method and application
By constructing a continuously inter-embedded MOF functional layer on the base membrane and coating it with an organosilicon protective layer, the problems of low flux, low separation coefficient and poor selectivity of MOF separation membranes are solved, and a highly efficient gas separation effect is achieved.
Patent Information
- Application Number
- CN202310333797.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-15
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2040-10-15
AI Technical Summary
Existing metal-organic framework (MOF) separation membranes suffer from problems such as discontinuous separation functional layers, weak bonding leading to easy detachment, low flux, low separation coefficient, and difficulty in improving selectivity for specific substances, and the preparation process is also discontinuous.
By performing specific pretreatment on the base membrane and combining it with in-situ growth reaction, a MOF functional layer with a continuous inter-intercalated structure is constructed, and an organosilicon protective layer is coated on the outside to form a polyhedral MOF separation membrane, thereby controlling its micro-geometry and chemical composition.
It improves the separation coefficient and service life of the separation membrane, enhances its antifouling ability, increases the membrane flux and selectivity, and achieves a more efficient gas separation effect.
Smart Images

Figure CN116474573B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a metal-organic framework material separation membrane and a method for preparing a metal-organic framework material separation membrane, belonging to the field of organic gas separation membrane preparation technology. Background Technology
[0002] Gas membrane separation technology is a new technology that utilizes the highly selective permeability of membrane materials to organic matter to achieve the separation of organic matter from the bulk gas phase. It offers advantages such as continuous process, no exothermic reaction, no secondary pollution, high recovery rate, low energy consumption, and miniaturization. This technology is currently the mainstream technology for organic matter separation and volatile organic compound (VOCs) treatment in developed countries, and it has very wide applications in environmental protection, chemical engineering, and biopharmaceutical fields.
[0003] Most existing organic gas separation membranes are prepared from siloxanes through coating and crosslinking processes, with polydimethylsiloxane (PDMS) being the most widely used. Block copolymers (PEBA) are also a commonly used functional layer material for organic gas separation membranes. They possess the rigidity of polyamide (PA) and the flexibility of polyether (PE). The flexible polyether provides high permeability, preferentially allowing organic matter to pass through; the rigid polyamide provides mechanical strength, overcoming membrane swelling caused by excessive adsorption of organic matter, thus maintaining good permeation selectivity. Currently, PDMS membranes have a high flux, but their loose molecular structure is difficult to control, resulting in a low separation coefficient and difficulty in improving the selectivity for specific substances. Although PEBA membranes possess the properties of both block molecules, their fixed molecular composition and simple structure usually result in a relatively dense structure, leading to a high separation coefficient but a low overall flux, which limits their applications.
[0004] As initially understood, "sieving mechanism" membranes achieve separation by strictly controlling the pore size, allowing only molecules smaller than the pore size to pass through while retaining larger molecules. Therefore, they offer high flux and high separation coefficients. However, since gas molecules are mostly smaller than 1 nanometer in diameter, and the differences in molecular diameter between gas molecules are very small, achieving precise sieving requires extremely high-precision membrane structures. Currently, no gas separation membrane based on a sieving mechanism is commercially available.
[0005] Metal-organic frameworks (MOFs) are a new type of porous material developed in recent years. Due to their advantages such as tunable pore size, high specific surface area, structural stability, and ease of functionalization, they have become a research hotspot for researchers both domestically and internationally. In the field of separation engineering, MOFs, as a novel adsorbent, have shown broad application prospects in the separation of organic matter and the removal and enrichment analysis of ions in water. However, using them solely for adsorption processes suffers from problems such as discontinuous processes, the need for desorption, difficult adsorbent regeneration, and short lifespan.
[0006] Patent CN 110052185 A discloses a modification method for a dopamine-based UiO-66 membrane. The method involves vertically immersing a porous substrate in a precursor solution prepared by dissolving zirconium chloride and terephthalic acid in N,N-dimethylformamide, using a fixture, and heat-treating at a constant temperature for 48-96 hours; followed by ultrasonic treatment for 3-30 seconds to obtain a substrate with seed crystals; the substrate with seed crystals is then heat-treated at least twice more in the same manner until a continuous UiO-66 membrane is obtained; the resulting membrane is then subjected to a first immersion and a second immersion to obtain a polydopamine-grafted UiO-66 membrane. The polydopamine-grafted UiO-66 membrane contains almost no intercalated UiO-66 structures, resulting in poor membrane density and difficulty in improving the selectivity for specific substances. Summary of the Invention
[0007] The purpose of this invention is to address the problems in existing technologies, such as difficulty in obtaining a continuous and complete MOF (Metal-Organic Framework) separation functional layer, weak bonding between the separation functional layer and the base membrane leading to detachment and defects, low flux, low separation coefficient, difficulty in improving selectivity for specific substances, and discontinuous preparation process. This invention constructs a continuously interlocking metal-organic framework material separation functional layer by performing specific pretreatment on the base membrane and combining it with in-situ growth reactions. This results in a membrane surface functional layer with a special micro-geometry, and allows for the control of its structure and chemical composition. Simultaneously, a silane coating solution is applied to this functional layer to form an organosilicon protective layer, filling any potential defects in the functional layer and preventing contamination and damage during use, thereby improving the separation coefficient and lifespan of the membrane. Furthermore, this results in a membrane surface with greater surface roughness and hydrophobicity, providing stronger antifouling capabilities and facilitating the contact, dissolution, and permeation of material molecules on the membrane surface, thus increasing membrane flux.
[0008] According to a first aspect of the present invention, a MOFs separation membrane is provided, the MOFs separation membrane comprising a base membrane and a MOFs functional layer, the MOFs functional layer structure comprising a plurality of inter-embedded polyhedral structures.
[0009] The inter-embedded polyhedral structure described in this invention refers to a part of the structure of a polyhedron being inserted into the interior of other polyhedral structures that are adjacent or close to it, or in other words, a polyhedron sharing a portion of its lattice with one or more surrounding polyhedra.
[0010] According to some embodiments of the present invention, the polyhedron is constructed from multiple lattices, and adjacent polyhedra in the interlocking polyhedron structure share a lattice.
[0011] According to some embodiments of the present invention, the distance between the centers of two adjacent polyhedra in the interlocking polyhedral structure is less than the average length L of the two adjacent polyhedra, preferably less than 0.95L, and more preferably 0.2-0.9L.
[0012] In this invention, "average value L" refers to half of the sum of the lengths of the two polyhedra. For example, if the length of polyhedron A is L1 and the length of polyhedron B is L2, then L = (L1 + L2) / 2.
[0013] According to some embodiments of the present invention, at least 20% of the polyhedra in the functional layer of the MOFs are inter-embedded, preferably at least 30%, preferably at least 40%, preferably at least 50%, preferably at least 60%, and preferably at least 80% of the polyhedra are inter-embedded.
[0014] According to some embodiments of the present invention, the polyhedron includes a hexahedral structure and / or an octahedral structure.
[0015] According to some embodiments of the present invention, the length of the polyhedron is 50-2000 nm.
[0016] According to some embodiments of the present invention, the polyhedron is constructed from multiple lattices, wherein the lattices are composed of metal atoms and organic ligands.
[0017] According to a preferred embodiment of the present invention, the metal atom is selected from zirconium atom, niobium atom, molybdenum atom or cobalt atom.
[0018] According to a preferred embodiment of the present invention, the organic ligand is selected from terephthalic acid or nitroterephthalic acid.
[0019] According to some embodiments of the present invention, the length of the hexahedron is 50-1000 nm, wherein the proportion of hexahedrons with a length of 400-600 nm is 50-80%.
[0020] According to some embodiments of the present invention, the length of the octahedron is 200-2000 nm, wherein the proportion of octahedrons with a length of 800-1200 nm is 60-80%.
[0021] In this invention, the "length of the polyhedron" refers to the maximum length between the vertices of the polyhedron.
[0022] According to some embodiments of the present invention, each octahedron or hexahedron is constructed from multiple lattices formed by multiple groups of zirconium metal atoms and terephthalic acid.
[0023] According to some embodiments of the present invention, the MOFs functional layer includes one or more interlocking polyhedral structures.
[0024] According to some embodiments of the present invention, the pore size of the MOF functional layer is determined by the average size of the lattice formed by the metal atoms and organic ligands.
[0025] According to some embodiments of the present invention, the average pore size of the MOFs functional layer is 0.1-2.0 nm, preferably 0.30-0.96 nm.
[0026] According to some embodiments of the present invention, the thickness of the MOF functional layer is 200-5000 nm.
[0027] According to some embodiments of the present invention, the thickness of the MOF functional layer is 1000-5000 nm.
[0028] According to some embodiments of the present invention, the base film is selected from one or more of polypropylene film, polyethylene film, polyvinyl chloride film or polytetrafluoroethylene film.
[0029] According to some embodiments of the present invention, the pore size of the base film is 10-10000 nm, preferably 50-5000 nm, and more preferably 200-1000 nm.
[0030] In some preferred embodiments of the present invention, the base film is a polypropylene film, polyethylene film, polyvinyl chloride film, or polytetrafluoroethylene film with a pore size of 50nm-5000nm, prepared by melt spinning stretching or thermally induced phase separation.
[0031] According to some embodiments of the present invention, the MOFs functional layer further includes an auxiliary functional layer.
[0032] According to some embodiments of the present invention, the auxiliary functional layer is a portion for repairing any areas where the embedded octahedral or embedded hexahedral structure may not be fully formed.
[0033] According to some embodiments of the present invention, the MOFs separation membrane further includes an organosilicon layer located on the surface of the functional layer of the metal-organic framework material.
[0034] According to a second aspect of the present invention, a method for preparing MOF separation membranes is provided, comprising the following steps:
[0035] (1) Prepare a solution comprising a first organic solvent, an organic ligand, a first metal compound and an auxiliary agent, wherein the auxiliary agent is selected from water or glacial acetic acid;
[0036] (2) Pre-treat the base film by introducing metal atoms from the first metal compound in step (1) onto its surface;
[0037] (3) The base membrane after pretreatment in step (2) is mixed with the solution in step (1) to obtain a first mixture. The first mixture is heated to react and a MOF separation membrane is obtained.
[0038] (4) Optionally, the separation membrane is cleaned to obtain the desired result.
[0039] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (10-1000):(1-100):(1-100).
[0040] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (100-1000):(1-10):(1-10).
[0041] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (100-700):1:1, for example 100:1:1, 200:1:1, 250:1:1, 300:1:1, 350:1:1, 420:1:1, 450:1:1, 550:1:1, 610:1:1, 650:1:1 and any value between them.
[0042] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (400-600):1:1.
[0043] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent and the auxiliary agent water is 100:(0.001-0.05), for example 100:0.01 or 100:0.03.
[0044] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent and the auxiliary agent glacial acetic acid is 100:(20-60), for example 100:25, 100:30, 100:40 or 100:50.
[0045] According to some embodiments of the present invention, the first organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide and dimethylacetamide.
[0046] According to some embodiments of the present invention, the organic ligand is selected from terephthalic acid and / or nitroterephthalic acid.
[0047] According to some embodiments of the present invention, the first metal compound is selected from one or more of zirconium compounds, niobium compounds, molybdenum compounds and cobalt compounds, preferably zirconium tetrachloride.
[0048] According to some embodiments of the present invention, the base film is selected from one or more of polypropylene film, polyethylene film, polyvinyl chloride film or polytetrafluoroethylene film.
[0049] According to some embodiments of the present invention, the pore size of the base film is 10-10000 nm, preferably 50-5000 nm, and more preferably 200-1000 nm.
[0050] In some preferred embodiments of the present invention, the base film is a polypropylene film, polyethylene film, polyvinyl chloride film, or polytetrafluoroethylene film with a pore size of 50nm-5000nm, prepared by melt spinning stretching or thermally induced phase separation.
[0051] According to some embodiments of the present invention, step (2) includes the following steps:
[0052] (2A-1) Prepare a solution containing polyacrylic acid, polyvinyl alcohol, and a second metal compound.
[0053] (2A-2) Coat the solution from step (2A-1) onto the base film.
[0054] According to some embodiments of the present invention, the polyacrylic acid includes polyacrylic acid and partially hydrolyzed polyacrylic acid.
[0055] According to some embodiments of the present invention, the mass concentration of polyacrylic acid and polyvinyl alcohol in the solution of step (2A-1) is 500-2000 mg / L.
[0056] According to some embodiments of the present invention, the molar ratio of the total amount of polyacrylic acid and polyvinyl alcohol in the solution of step (2A-1) to the molar ratio of the metal compound is 1-3:1.
[0057] According to some embodiments of the present invention, the metal atoms in the second metal compound are the same as the metal atoms in the first metal compound in step (1). Preferably, the second metal compound is selected from one or more of zirconium compounds, niobium compounds, molybdenum compounds and cobalt compounds, and preferably zirconium tetrachloride.
[0058] According to some embodiments of the present invention, in step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 0.1-10 m². 2 / L, for example 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m 2 / L, 5.0m 2 / L, 5.5m 2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L and any values in between.
[0059] According to some embodiments of the present invention, in step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 0.5-5 m². 2 / L.
[0060] In some preferred embodiments of the present invention, in step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 1-2 m². 2 / L.
[0061] In some preferred embodiments of the present invention, step (2) includes the following specific steps:
[0062] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the mixed solution.
[0063] (b) The solution generated in (a) is coated onto the surface of the base film and then dried to allow a certain amount of metal atoms to adhere to the surface of the base film.
[0064] According to some embodiments of the present invention, step (2) includes the following steps:
[0065] (2B-1) Prepare a solution comprising the metal complex shown in Formula I and a second organic solvent.
[0066] (2B-2) Mix the base film with the solution from step (2B-1).
[0067] (2B-3) The base film after mixing in step (2B-2) is cleaned with the third solvent;
[0068]
[0069] In Formula I, Q is selected from amide group, carbonyl group or C1-C6 alkylene group; R1 is selected from hydrogen, C1-C6 alkyl group, C1-C6 alkoxy group or halogen; M1 is the same as the metal atom in the first metal compound in step (1), preferably M1 is selected from zirconium atom, niobium atom, molybdenum atom or cobalt atom; m is 5-20; n is 1-10.
[0070] According to some embodiments of the present invention, in Formula I, Q is selected from an amide group, R1 is selected from a C3-C6 alkyl group, m is 5-20, and n is 1-10.
[0071] According to some embodiments of the present invention, the metal complex represented by Formula I is:
[0072] m = 5 - 20, n = 1 - 10.
[0073] According to some embodiments of the present invention, the metal complex represented by Formula I is:
[0074] m = 5 - 20, n = 1 - 10.
[0075] According to some embodiments of the present invention, the second organic solvent is selected from one or more organic solvents capable of causing the base film to swell, preferably selected from one or more of C5-C10 aliphatic hydrocarbons, C1-C10 halogenated aliphatic hydrocarbons, C6-C20 aromatic hydrocarbons and C6-C20 halogenated aromatic hydrocarbons, more preferably selected from one or more of n-pentane, n-hexane, chloroform, carbon tetrachloride, benzene and toluene.
[0076] According to some embodiments of the present invention, the third solvent is selected from one or more solvents capable of deswelling the swollen base film, preferably water.
[0077] According to some embodiments of the present invention, in the solution of step (2B-1), the mass concentration of the metal complex represented by Formula I is 500-2000 mg / L.
[0078] According to some embodiments of the present invention, in step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 0.1-10 m². 2 / L, for example 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m 2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m 2 / L, 5.0m 2 / L, 5.5m 2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L and any values in between.
[0079] According to some embodiments of the present invention, in step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 0.5-5 m². 2 / L.
[0080] In some advantageous embodiments of the present invention, in step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 1-2 m². 2 / L.
[0081] In some preferred embodiments of the present invention, step (2) includes the following specific steps:
[0082] (a) Dissolve the acrylic acid-N-tert-butylacrylamide / zirconium complex in n-hexane at a mass concentration of 1000 mg / L to prepare a homogeneous solution;
[0083] (b) Immerse the base membrane in the solution of step (a) for 1-24 hours, remove it and quickly transfer it to deionized water for washing. After drying, the modified base membrane is obtained. At this time, a portion of the acrylic acid-N-tert-butylacrylamide / zirconium complex is embedded in the surface layer of the embedded base membrane structure, introducing a certain amount of relatively stable zirconium atoms into the base membrane.
[0084]
[0085] According to some embodiments of the present invention, step (2) includes the following steps:
[0086] (2C-1) Prepare a solution containing the metal complex shown in Formula II.
[0087] (2C-2) The base film is mixed with the solution from step (2C-1) to obtain a mixture, and the mixture is subjected to a polymerization reaction under microwave radiation conditions;
[0088]
[0089] In Formula II, X is selected from amide, carbonyl or C1-C6 alkylene groups; R2, R3 and R4 are the same or different, and are each independently selected from hydrogen, C1-C6 alkyl, C1-C6 alkoxy or halogen; M2 is the same as the metal atom in the first metal compound in step (1), preferably M2 is selected from zirconium atom, niobium atom, molybdenum atom or cobalt atom.
[0090] According to some embodiments of the present invention, in Formula II, X is selected from an amide group; R2, R3 and R4 may be the same or different, and each is independently selected from hydrogen or C1-C3 alkyl groups.
[0091] According to some embodiments of the present invention, the metal complex represented by Formula II is:
[0092]
[0093] According to some embodiments of the present invention, the metal complex represented by Formula II is:
[0094]
[0095] According to some embodiments of the present invention, the solution of the metal complex in step (2C-1) is an aqueous solution of the metal complex.
[0096] According to some embodiments of the present invention, in the solution of step (2C-1), the mass concentration of the metal complex represented by formula II is 500-20000 mg / L.
[0097] According to some embodiments of the present invention, in step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 0.1-10 m². 2 / L, for example 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m 2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m 2 / L, 5.0m 2 / L, 5.5m2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L and any values in between.
[0098] According to some embodiments of the present invention, in step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 0.5-5 m². 2 / L.
[0099] According to some preferred embodiments of the present invention, in step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 1-2 m². 2 / L.
[0100] According to some embodiments of the present invention, in step (2C-2), the microwave intensity of the microwave radiation is 500-2000 μw / cm. 2 .
[0101] According to some embodiments of the present invention, in step (2C-2), the microwave frequency of the microwave radiation is 1000-200000Hz.
[0102] In some preferred embodiments of the present invention, step (2) includes the following specific steps:
[0103] (a) The acrylic acid-N-bispropyleneamine / zirconium complex was dissolved in an aqueous solution to prepare a graft polymerization solution;
[0104] (b) Immerse the base film in the graft polymerization solution prepared in step (a);
[0105] (c) Radiation grafting polymerization is carried out under microwave radiation of a certain intensity, which initiates the generation of free radicals on the base film and the grafting polymerization reaction with the double bonds in the acrylic acid-N-bispropyleneamine / zirconium complex in the grafting polymerization solution, thereby obtaining a modified base film and introducing zirconium atoms on the surface.
[0106]
[0107] In this invention, by pretreating the base film, metal atoms can be introduced onto the base film, so that the MOFs functional layer is firmly bonded to the base film. On the other hand, the metal atoms introduced onto the base film can provide metal nodes for the subsequent in-situ growth of the MOFs functional layer, so that an inter-embedded structure will appear during the growth of the MOFs functional layer, thus avoiding the generation of defects.
[0108] According to some embodiments of the present invention, in step (3), the ratio of the surface area of the base film after pretreatment in step (2) to the volume of the solution obtained in step (1) is (0.01-100) m². 2 / L, preferably (0.01-10)m 2 / L; more preferably 0.5-2m 2 / L.
[0109] According to a preferred embodiment of the present invention, in step (3), before adding the base membrane to the solution obtained in step (1), it can be treated as follows: the surface of the base membrane (or the prepared membrane module) is washed with water and an organic solvent in sequence and then dried; the organic solvent is preferably ethanol, methanol or acetone; preferably, the base membrane (or the prepared membrane module) is washed with water twice, washed with organic solvent twice and then dried.
[0110] According to some embodiments of the present invention, step (3) includes:
[0111] The first mixture is heated to react the organic ligands and the metal compound, generating MOF materials on the surface of the base membrane, thus obtaining the separation membrane.
[0112] According to a preferred embodiment of the present invention, in step (3), the reaction temperature is 50-300℃; preferably, the reaction temperature is 100-200℃.
[0113] According to a preferred embodiment of the present invention, in step (3), the reaction pressure is 0.01-0.5 MPa (gauge pressure), preferably 0.05-0.1 MPa (gauge pressure).
[0114] According to a preferred embodiment of the present invention, in step (3), the reaction time is 1-100h, for example 5h, 17h, 20h, 25h, 27h, 30h, 40h, 50h, 60h, 70h, 80h, 90h and any value between them.
[0115] According to a preferred embodiment of the present invention, in step (3), the reaction time is 10-72h, preferably 15-30h.
[0116] According to a preferred embodiment of the present invention, step (3) can be performed in an inert gas atmosphere, preferably nitrogen.
[0117] According to some embodiments of the present invention, in step (4), the separation membrane is removed (or the polymerization solution in the membrane module is discharged); the surface of the membrane after the reaction is washed multiple times with organic solvent and water to remove unreacted monomers and solvents, and MOF organic gas separation membrane (or membrane module) is obtained. The organic solvent used to wash the membrane surface includes ethanol, methanol or acetone; preferably, the separation membrane is washed twice with water and twice with organic solvent and then dried.
[0118] According to some embodiments of the present invention, the method for preparing MOF separation membranes of the present invention further includes the following steps:
[0119] (5) Perform one or more repair treatments on the MOFs separation membrane obtained in step (3) or (4), preferably the repair treatment includes:
[0120] (A) The MOF separation membrane is mixed with a solution containing a first organic solvent, an organic ligand, a first metal compound and an additive to obtain a second mixture, wherein the additive is selected from water or glacial acetic acid;
[0121] (B) The second mixture is heated to produce a reaction and a MOF separation membrane is obtained.
[0122] (C) Optionally, the separation membrane is cleaned to obtain the desired result.
[0123] According to some embodiments of the present invention, step (A) includes:
[0124] (A1) Prepare a solution comprising a first organic solvent, an organic ligand, a first metal compound, and an auxiliary agent, wherein the auxiliary agent is selected from water or glacial acetic acid;
[0125] (A2) Add the MOFs separation membrane obtained in step (2) or (3) to the solution obtained in step (A1) to obtain a second mixture.
[0126] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (10-1000):(1-100):(1-100); preferably (100-1000):(1-10):(1-10), more preferably (100-700):1:1, for example 100:1:1, 200:1:1, 250:1:1, 300:1:1, 350:1:1, 400:1:1, 420:1:1, 550:1:1 or 600:1:1, 1, 650:1:1 and any value between them.
[0127] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the first organic solvent to the auxiliary agent water is 100:(0.001-0.05), for example 100:0.01 or 100:0.03.
[0128] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the first organic solvent and the auxiliary agent glacial acetic acid is 100:(20-60), for example 100:25, 100:30, 100:40 or 100:50.
[0129] According to a preferred embodiment of the present invention, in step (A2), the ratio of the surface area of the MOF separation membrane to the volume of the solution in step (A1) is (0.01-100) m². 2 / L; preferably (0.01-10)m 2 / L; more preferably 1m 2 / L.
[0130] According to a preferred embodiment of the present invention, step (B) includes:
[0131] The second mixture is heated to react the organic ligands and the first metal compound, and MOFs material is further generated on the surface of the MOFs organic gas separation membrane, thus obtaining the final product.
[0132] According to a preferred embodiment of the present invention, in step (B), the reaction temperature is 50-300°C, the reaction pressure is 0.01-0.5 MPa (gauge pressure), and the reaction time is 1-100 h.
[0133] According to a preferred embodiment of the present invention, in step (B), the reaction temperature is 100-200°C, the reaction pressure is 0.05-0.1 MPa (gauge pressure), and the reaction time is 5-50 h.
[0134] According to a preferred embodiment of the present invention, in step (B), the reaction time is 10-20 hours.
[0135] According to a preferred embodiment of the present invention, step (B) can be performed in an inert gas atmosphere, preferably nitrogen.
[0136] According to some embodiments of the present invention, in step (C), the separation membrane is removed (or the polymerization solution in the membrane module is drained); the surface of the membrane after the reaction is washed multiple times with an organic solvent and water to remove unreacted monomers and solvents, thereby obtaining an MOF organic gas separation membrane (or membrane module). The organic solvent used to wash the membrane surface includes ethanol, methanol, or acetone. Preferably, the separation membrane is washed twice with water, twice with organic solvent, and then dried.
[0137] According to some embodiments of the present invention, the method for preparing MOFs separation membrane of the present invention further includes the following steps: coating the surface of the MOFs separation membrane obtained in step (3) or (4) or (B) or (C) with silane coating liquid, heating the MOFs separation membrane coated with silane coating liquid to cause the silane coating liquid to undergo a crosslinking reaction, thereby obtaining a MOFs separation membrane including an organosilicon layer.
[0138] According to some embodiments of the present invention, the silane coating liquid can be coated onto the surface of the MOFs separation membrane obtained in step (4) or step (C) by dip coating, scraping or other methods, so that the surface of the MOFs separation membrane is coated with a silane coating liquid with a thickness of 1-100 micrometers, preferably 25 micrometers.
[0139] According to some embodiments of the present invention, the temperature of the crosslinking reaction is 50-300°C, preferably 50-200°C, more preferably 150°C; and the time is 0.1-20h, preferably 0.1-10h, more preferably 0.5h.
[0140] After the cross-linking reaction, a cross-linked silane protective layer is formed on the surface of the MOF organic gas separation membrane.
[0141] According to some embodiments of the present invention, the preparation of the silane coating solution includes the following steps:
[0142] S1, mix and dissolve silane, crosslinking agent and organic solvent to obtain a mixture;
[0143] S2, a catalyst is added to the mixture to allow it to undergo pre-crosslinking, resulting in a silane coating solution.
[0144] According to some embodiments of the present invention, the ratio of silane, crosslinking agent and organic solvent in step S1 is (0.1-10):(0.1-10):(90-100), preferably (1-10):(1-10):(90-100), and more preferably 9:1:90.
[0145] According to a preferred embodiment of the present invention, the silane may be a monomer of siloxane material, including one or more of dimethylsiloxane, cured silicone rubber, and vulcanized silicone rubber mixed in any proportion; and / or, the crosslinking agent includes tetraethyl orthosilicate or tetramethoxysilane; and / or, the organic solvent includes at least one of heptane, pentane, toluene, benzene, xylene, and hexane, preferably n-hexane.
[0146] According to a preferred embodiment of the present invention, the catalyst may be an organotin catalyst such as dibutyltin dilaurate or a titanium complex catalyst such as tetrabutyl titanate; the amount of the catalyst is 0.01-1 wt%, preferably 0.01-0.1 wt%.
[0147] According to some embodiments of the present invention, the pre-crosslinking time in step S2 is 1-48h, preferably 10-30h, more preferably 24h; and / or, the viscosity of the silane coating liquid is 100-50000mPa.s, preferably 100-5000mPa.s, more preferably 2000mPa.s.
[0148] According to some embodiments of the present invention, the method for preparing MOF separation membranes of the present invention further includes the following steps:
[0149] The prepared MOF separation membrane is treated with an alkaline solution to control its pore size. The control process breaks the chemical bonds between some zirconium atoms and organic matter, increases the permeability of the functional layer and the interconnectivity of the internal lattice, and obtains the required separation pore size and a more suitable flux.
[0150] According to some embodiments of the present invention, the alkaline solution is preferably a sodium hydroxide solution with a pH of 9-13; the addition process is accompanied by stirring, and the flow rate obtained by stirring is 0.01-1 m / s, preferably 0.1 m / s. The stirring time is 10-120 min, preferably 30-60 min.
[0151] According to a third aspect of the present invention, a MOFs separation membrane prepared by the method for preparing MOFs separation membranes described in the second aspect is provided.
[0152] According to a fourth aspect of the present invention, the application of the MOFs separation membrane described in the first aspect or the MOFs separation membrane prepared by the method described in the second aspect is provided in the fields of petrochemical, biological, pharmaceutical, energy and environmental protection, especially in the separation of organic matter.
[0153] According to some embodiments of the present invention, the MOFs separation membrane can be used for the separation of benzene-related organic compounds such as benzene, toluene, and xylene.
[0154] According to some embodiments of the present invention, the MOFs separation membrane can be used for the separation of alkanes such as methane, ethane, propane, butane, pentane, hexane, heptane, cyclohexane, and isopentane, as well as unsaturated alkanes such as ethylene, propylene, acetylene, butene, and styrene, and their volatile gases from nitrogen and air.
[0155] According to some embodiments of the present invention, the separation can be a single-stage or multi-stage membrane separation.
[0156] According to some embodiments of the present invention, in helium purification and separation, the MOFs separation membrane can be used in conjunction with cryogenic, dehydrogenation, and deoxygenation processes.
[0157] According to some embodiments of the present invention, in the separation of olefins and alkanes, the MOF separation membrane can be used in conjunction with cryogenics, distillation, and PSA.
[0158] According to some embodiments of the present invention, in the field of organic gas separation, the MOFs separation membrane can be developed into a complete process using technologies such as condensation, adsorption, and absorption.
[0159] Compared with existing technologies, the MOFs separation membrane and its preparation method provided by this invention have the following advantages:
[0160] (1) The preparation process is simple, easy to operate, and low in cost;
[0161] (2) The prepared MOF functional layer has excellent chemical resistance, high temperature resistance and high mechanical strength;
[0162] (3) The polyhedra in the functional layer of MOFs are inter-embedded, spread on the surface of the base film, dense and continuous, thin and uniform in pore size distribution, which makes the membrane have a large flux and a high separation coefficient.
[0163] (4) The silicone protective layer is hydrophobic and breathable, which can prevent water vapor and particulate matter from damaging the functional layer of MOFs;
[0164] (5) The high-performance organic gas separation membrane prepared by the method described in this invention has been well applied in the fields of petrochemical, biological, pharmaceutical, energy and environmental protection due to its excellent properties. Attached Figure Description
[0165] Figure 1 This shows an electron microscope image of the surface of the MOF organic gas separation membrane prepared in Example 1;
[0166] Figure 2 This shows an electron microscope image of the surface of the MOF organic gas separation membrane prepared in Example 5;
[0167] Figure 3 This shows an electron microscope image of the surface of the MOF organic gas separation membrane prepared in Example 9;
[0168] Figure 4 This shows an electron micrograph of the surface of the MOF organic gas separation membrane prepared in Example 13;
[0169] Figure 5 This shows an electron micrograph of the surface of the MOF organic gas separation membrane prepared in Example 21;
[0170] Figure 6 This is a photograph of the polyvinylidene fluoride (PVDF) substrate in Comparative Example 1 after it has been immersed in the precursor solution.
[0171] Figure 7 This is a photograph of the polyvinylidene fluoride (PVDF) substrate in Comparative Example 2 after it has been immersed in the precursor solution.
[0172] Figure 8 This shows an electron microscope image of the surface of the MOF organic gas separation membrane prepared in Comparative Example 3;
[0173] Figure 9 This shows an electron microscope image of the surface of the MOF organic gas separation membrane prepared in Comparative Example 4;
[0174] Figure 10 The diagram shows a membrane performance testing device. The meanings of the labels in the diagram are as follows: 1. Purge gas; 2. Feed gas; 3. Temperature sensor; 4. Humidity sensor; 5. Membrane module; 6. Pressure gauge; 7. Gas chromatograph; 8. Soap film flow meter. Detailed Implementation
[0175] The present invention will be further illustrated below through embodiments, but is not limited to these embodiments.
[0176] Unless otherwise specified, all raw materials used in the examples are commercially available, and all chemicals mentioned are common chemicals in the prior art.
[0177] (1) The structural formula of the acrylic acid-N-tert-butylacrylamide / zirconium complex in the examples is shown below:
[0178] m = 12, n = 1;
[0179] Preparation method: Weigh 47g of acrylic acid and dissolve it in 250g of deionized water. Adjust the pH to 7-9 with NaOH solution. Take 50g of deionized water, add 12g of sodium dodecyl sulfate (SDS) and 8.9g of nonylphenol polyoxyethylene ether (NP), and add 3g of tert-butylacrylamide monomer dropwise while stirring continuously until a homogeneous and stable clear solution is formed. Mix the two solutions and place them in an adiabatic polymerization reactor. After purging with nitrogen for about 10 minutes to remove oxygen, add the redox initiator: ammonium persulfate-sodium bisulfite (each reagent is added at 0.05g of solid pure product to prepare a 1% deionized water solution). After the solution becomes viscous, stop the aeration and allow the temperature to rise naturally for the reaction. After 6-8 hours, the reaction is complete. Take the product hydrogel, cut it into small pieces, dry it at 50℃, and grind it into powder to obtain the acrylic acid-tert-butylacrylamide copolymer. Dissolve the copolymer in water at a certain concentration and add zirconium acetate to obtain the above-mentioned polyacrylic acid complexed zirconium-tert-butylacrylamide copolymer.
[0180] (2) The structural formula of the acrylic acid-N-bispropyleneamine / zirconium complex in the examples is shown below:
[0181]
[0182] Preparation method: Weigh 120g of acrylic acid and dissolve it in 80g of deionized water. Adjust the pH to 7-9 with NaOH solution. Take 20g of deionized water and add 6g of methylenebisacrylamide to form a homogeneous and stable clear solution, i.e., the first aqueous phase. Take 95g of industrial No. 5 white oil and add appropriate amounts of 7.65g of Span 80 and 10g of Tween 80, stirring to form a stable and homogeneous oil phase solution. Mix the first aqueous phase and oil phase, emulsify with an emulsifier to form a stable reverse emulsion, and place it in a polymerization reactor for cooling. First, add ammonium persulfate initiator solution (0.05g of ammonium persulfate, prepared as a 1% deionized water solution). Under uniform stirring and nitrogen protection, slowly add sodium bisulfite solution (0.05g pure solid, prepared as a 1% deionized water solution) and the second portion of methylenebisacrylamide solution. The reaction exhibits a slight exothermic phenomenon. After the addition is complete, continue stirring for 2 hours. The emulsion was then removed and poured into isopropanol / acetone (a mixture of isopropanol and acetone in any proportion), resulting in a white precipitate. The precipitate was centrifuged and washed with ethanol to obtain a copolymer of acrylic acid and methylenebisacrylamide. The copolymer was dissolved in water, and zirconium acetate was added to obtain an acrylic acid-N-bisacrylamide / zirconium complex solution.
[0183] Test methods
[0184] The membrane separation performance of the nitrogen / organic vapor mixture was tested using the analytical method described in the literature (Research on Hollow Fiber Composite Membrane Separation System for Organic Vapor / Nitrogen, He Chunhong, Tianjin University, 2005). The testing apparatus was as follows: Figure 10 As shown.
[0185] A typical structure of a gas separation membrane consists of a porous support covered with an extremely thin, dense layer. The true thickness of this dense layer is difficult to determine accurately; therefore, the permeability coefficient and the effective membrane thickness are often used together, and their ratio is called the permeation rate, calculated by the following formula:
[0186] J i =(P / l) i =Q i / (Δp·A) (1-1)
[0187] In the above formula, J i The permeation rate of gas component i is expressed in mol / (m²). 2 ·s·Pa); P is the permeability coefficient of gas component i, in units of mol·m / (m 2 ·s·Pa); l is the effective thickness of the membrane, in meters; Q i Δp is the molar flow rate of component i in the permeate gas under standard conditions, in mol / s; Δp is the osmotic pressure difference, in Pa; A is the membrane area, in m². 2 .
[0188] The separation coefficient α is calculated using the following formula.
[0189] α N2有机气体 =J N2 / J 有机气体 (1-2)
[0190]
Example 1
[0191] (1) Solution required for MOF functional layer preparation
[0192] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 400:1:1:0.01 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0193] (2) Base film pretreatment
[0194] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0195] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0196] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain the separation membrane.
[0197] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0198] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0199] The electron microscope images of the prepared film surface are as follows: Figure 1 ,from Figure 1As can be seen, the MOFs functional layer of the prepared membrane is composed of intercalated octahedral crystals, which spread, are dense and continuous on the surface of the base film, have high surface roughness, completely cover the base film, and have few defects in the functional layer.
[0200] The membrane performance test data are shown in Table 1. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 4.828 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.301 × 10⁻⁶ s·Pa, while the flux of propylene gas is only 0.301 × 10⁻⁶ s·Pa. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 16.03 (·s·Pa).
[0201]
Example 2
[0202] The only difference from Example 1 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., coating 1L of the solution generated in step (a) onto a membrane with a surface area of 0.1 square meters), and coating the dried base membrane surface with the solution generated in (a).
[0203] The membrane performance test data are shown in Table 1. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 2.01 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.18 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.18 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 11.17 (·s·Pa).
[0204]
Example 3
[0205] The only difference from Example 1 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 5m. 2 / L (i.e., coating a 5 square meter film with 1L of the solution generated in step (a)), and coating the dried base film surface with the solution generated in (a).
[0206] The membrane performance test data are shown in Table 1. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 10.41 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 1.206 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 1.206 × 10⁻⁶ Pa·s. - 6 mol / (m2 The nitrogen / propylene separation coefficient is 8.63 (·s·Pa).
[0207]
Example 4
[0208] The only difference from Example 1 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 10m². 2 / L (i.e., coating a 10 square meter film surface with 1L of the solution generated in step (a)), and coating the dried base film surface with the solution generated in (a).
[0209] The membrane performance test data are shown in Table 1. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 17.733 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is 1.909 × 10⁻⁶ s·Pa, while the flux of propylene gas is 1.909 × 10⁻⁶ s·Pa. -6 mol / (m 2 The nitrogen / propylene separation coefficient is 9.29 (·s·Pa).
[0210] Table 1
[0211]
[0212]
Example 5
[0213] (1) Solution required for MOF functional layer preparation
[0214] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 400:1:1:0.01 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0215] (2) Base film pretreatment
[0216] (a) Dissolve the acrylic acid-N-tert-butylacrylamide / zirconium complex in n-hexane at a mass concentration of 1000 mg / L to prepare a homogeneous solution;
[0217] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed into 1L of the solution generated in step (a)). The dried base membrane is immersed in the solution generated in (a) for 2 hours. After being taken out, it is quickly transferred to deionized water for washing. After drying, the modified base membrane is obtained. At this time, a portion of the acrylic acid-N-tert-butylacrylamide / zirconium complex is embedded in the surface layer of the embedded base membrane structure, introducing a certain amount of relatively stable zirconium atoms into the base membrane.
[0218] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 200°C for 24 hours to obtain the separation membrane.
[0219] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0220] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0221] The electron microscope images of the prepared film surface are as follows: Figure 2 .
[0222] The membrane performance test data are shown in Table 2. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.521 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.088 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.088 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 17.28 (·s·Pa).
[0223]
Example 6
[0224] The only difference from Example 5 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., a membrane with a surface area of 0.1 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0225] The membrane performance test data are shown in Table 2. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.01 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.12 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.12 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 8.42 (·s·Pa).
[0226]
Example 7
[0227] The only difference from Example 5 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution described in (a) is 5m². 2 / L (i.e., a membrane with a surface area of 5 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0228] The membrane performance test data are shown in Table 2. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 2.89 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.188 × 10⁻⁶ s·Pa, while the flux of propylene gas is only 0.188 × 10⁻⁶ s·Pa. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 15.37 (·s·Pa).
[0229]
Example 8
[0230] The only difference from Example 5 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution described in (a) is 10m². 2 / L (i.e., a membrane with a surface area of 10 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0231] The membrane performance test data are shown in Table 2. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 3.50 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.215 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.215 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 16.28 (·s·Pa).
[0232] Table 2
[0233]
[0234]
Example 9
[0235] (1) Solution required for MOF functional layer preparation
[0236] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 100:1:1:0.001 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0237] (2) Base film pretreatment
[0238] (a) The acrylic acid-N-bispropyleneamine / zirconium complex was dissolved in a solution and the grafting polymerization solution was prepared by dissolving it in water at a mass concentration of 1000 mg / L.
[0239] (b) After washing with water and ethanol and drying, a 500 nm pore size polypropylene hollow fiber base membrane was used. The ratio of the base membrane surface area to the solution generated in (a) was 1 m². 2 / L (i.e., 1L of the solution generated in step (a) is placed into a membrane with a surface area of 1 square meter), and the dried base membrane is immersed in the solution generated in (a) at 1000 μw / cm 2 Radiation grafting polymerization was carried out for 2 hours under microwave radiation with an intensity frequency of 1000-200000Hz. This triggered the generation of free radicals on the methyl groups on the polypropylene microporous membrane to undergo grafting polymerization with the double bonds in the acrylic acid-N-bispropyleneeneamine / zirconium complex in the grafting polymerization solution, thereby obtaining a modified base film and introducing zirconium atoms on the surface.
[0240] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 200°C for 24 hours to obtain the separation membrane.
[0241] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0242] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0243] The electron microscope images of the prepared film surface are as follows: Figure 3 .
[0244] The membrane performance test data are shown in Table 3. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.41 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.047 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.047 × 10⁻⁶. - 6 mol / (m 2 (·s·Pa), the nitrogen / propylene separation coefficient is 30.00.
[0245]
Example 10
[0246] The only difference from Example 9 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., a membrane with a surface area of 0.1 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0247] The membrane performance test data are shown in Table 3. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.341 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.0114 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.0114 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 29.91 (·s·Pa).
[0248]
Example 11
[0249] The only difference from Example 9 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 5m. 2 / L (i.e., a membrane with a surface area of 5 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0250] The membrane performance test data are shown in Table 3. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.884 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.074 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.074 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 25.46 (·s·Pa).
[0251]
Example 12
[0252] The only difference from Example 9 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 10m². 2 / L (i.e., a membrane with a surface area of 10 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0253] The membrane performance test data are shown in Table 3. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 2.984 × 10⁻⁶. -6 mol / (m 2The flux of propylene gas is only 0.121 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.121 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 24.66 (·s·Pa).
[0254] Table 3
[0255]
[0256]
[0257]
Example 13
[0258] (1) Solution required for MOF functional layer preparation
[0259] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid were mixed in a molar ratio of 400:1:1:150 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0260] (2) Base film pretreatment
[0261] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0262] (b) After washing with water and ethanol and drying, a polyethylene hollow fiber base membrane with a pore size of 500 nm was used. The ratio of the base membrane surface area to the solution generated in (a) was 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0263] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 200°C for 24 hours to obtain the separation membrane.
[0264] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0265] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0266] The electron microscope images of the prepared film surface are as follows: Figure 4 .
[0267] The membrane performance test data are shown in Table 4. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.896 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.047 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.047 × 10⁻⁶. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 19.06 (·s·Pa).
[0268]
Example 14
[0269] The only difference from Example 13 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., coating 1L of the solution generated in step (a) onto a membrane with a surface area of 0.1 square meters), and coating the dried base membrane surface with the solution generated in (a).
[0270] The membrane performance test data are shown in Table 4. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.288 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.0095 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.0095 × 10⁻⁶. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 30.32 (·s·Pa).
[0271]
Example 15
[0272] The only difference from Example 13 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 5m². 2 / L (i.e., coating a 5 square meter film with 1L of the solution generated in step (a)), and coating the dried base film surface with the solution generated in (a).
[0273] The membrane performance test data are shown in Table 4. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.208 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.1659 × 10⁻⁶ s·Pa, while the flux of propylene gas is only 0.1659 × 10⁻⁶ s·Pa. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 7.28 (·s·Pa).
[0274]
Example 16
[0275] The only difference from Example 13 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 10m². 2 / L (i.e., coating a 10 square meter film surface with 1L of the solution generated in step (a)), and coating the dried base film surface with the solution generated in (a).
[0276] The membrane performance test data are shown in Table 4. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.48 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.2659 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.2659 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 5.57 (·s·Pa).
[0277] Table 4
[0278]
[0279]
Example 17
[0280] (1) Solution required for MOF functional layer preparation
[0281] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid were mixed in a molar ratio of 200:1:1:100 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0282] (2) Base film pretreatment
[0283] (a) Dissolve the acrylic acid-N-tert-butylacrylamide / zirconium complex in n-hexane at a mass concentration of 1000 mg / L to prepare a homogeneous solution;
[0284] (b) After washing with water and ethanol and drying, a polyethylene hollow fiber base membrane with a pore size of 500 nm was used. The ratio of the base membrane surface area to the solution generated in (a) was 10 m² / 200 nm. 2 / L (i.e., a membrane with a surface area of 10 square meters is placed into 1L of the solution generated in step (a)). The dried base membrane is immersed in the solution generated in (a) for 10 hours. After removal, it is quickly transferred to deionized water for washing. After removal and drying, the modified base membrane is obtained. At this time, a portion of the acrylic acid-N-tert-butylacrylamide / zirconium complex is embedded in the surface layer of the embedded base membrane structure, introducing a certain amount of relatively stable zirconium atoms into the base membrane.
[0285] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 200°C for 24 hours to obtain the separation membrane.
[0286] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0287] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0288] The membrane performance test data are shown in Table 5. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 2.468 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.115 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.115 × 10⁻⁶. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 21.46 (·s·Pa).
[0289]
Example 18
[0290] The only difference from Example 17 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., a membrane with a surface area of 0.1 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0291] The membrane performance test data are shown in Table 5. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.3008 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.0184 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.0184 × 10⁻⁶. -6 mol / (m 2 The nitrogen / propylene separation coefficient is 16.35 (·s·Pa).
[0292]
Example 19
[0293] The only difference from Example 17 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 1m. 2 / L (i.e., a membrane with a surface area of 1 square meter is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0294] The membrane performance test data are shown in Table 5. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.241 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.038 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.038 × 10⁻⁶. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 32.66 (·s·Pa).
[0295]
Example 20
[0296] The only difference from Example 17 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 5m. 2 / L (i.e., a membrane with a surface area of 5 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a).
[0297] The membrane performance test data are shown in Table 5. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 2.198 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.087 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.087 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 25.26 (·s·Pa).
[0298] Table 5
[0299]
[0300]
Example 21
[0301] (1) Solution required for MOF functional layer preparation
[0302] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid were mixed in a molar ratio of 1000:1:1:500 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0303] (2) Base film pretreatment
[0304] (a) The acrylic acid-N-bispropyleneamine / zirconium complex was dissolved in a solution and a graft polymerization solution was prepared by dissolving it in pure water at a mass concentration of 1000 mg / L.
[0305] (b) After washing with water and ethanol and drying, a polyethylene hollow fiber base membrane with a pore size of 500 nm was used. The ratio of the base membrane surface area to the solution generated in (a) was 1 m². 2 / L (i.e., 1L of the solution generated in step (a) is placed into a membrane with a surface area of 1 square meter), and the dried base membrane is immersed in the solution generated in (a) at 1000 μw / cm 2 Radiation grafting polymerization was carried out for 2 hours under microwave radiation with an intensity frequency of 1000-200000Hz. This triggered the generation of free radicals on the methyl groups on the polypropylene microporous membrane to undergo grafting polymerization with the double bonds in the acrylic acid-N-bispropyleneeneamine / zirconium complex in the grafting polymerization solution, thereby obtaining a modified base film and introducing zirconium atoms on the surface.
[0306] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 200°C for 24 hours to obtain the separation membrane.
[0307] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0308] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0309] The electron microscope images of the prepared film surface are as follows: Figure 5 .
[0310] The membrane performance test data are shown in Table 6. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.889 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.042 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.042 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 21.17 (·s·Pa).
[0311]
Example 22
[0312] The only difference from Example 21 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 0.1 m². 2 / L (i.e., a membrane with a surface area of 0.1 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0313] The membrane performance test data are shown in Table 6. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 0.152 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.0112 × 10⁻⁶ (·s·Pa), while the flux of propylene gas is only 0.0112 × 10⁻⁶. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 13.57 (·s·Pa).
[0314]
Example 23
[0315] The only difference from Example 21 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 5m. 2 / L (i.e., a membrane with a surface area of 5 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0316] The membrane performance test data are shown in Table 6. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.055 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.087 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.087 × 10⁻⁶ Pa·s. - 6 mol / (m 2 The nitrogen / propylene separation coefficient is 12.13 (·s·Pa).
[0317]
Example 24
[0318] The only difference from Example 21 is that in (2) the base film pretreatment, the ratio of the base film surface area to the solution generated in (a) is 10m². 2 / L (i.e., a membrane with a surface area of 5 square meters is placed into 1L of the solution generated in step (a)), and the dried base membrane is immersed in the solution generated in (a) for radiation graft polymerization.
[0319] The membrane performance test data are shown in Table 6. The test data indicates that the nitrogen flux in a propylene and nitrogen mixture at 0.1 MPa can reach 1.386 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.114 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.114 × 10⁻⁶ Pa·s. - 6 mol / (m2 The nitrogen / propylene separation coefficient is 12.16 (·s·Pa).
[0320] Table 6
[0321]
[0322]
Examples 25-29
[0323] (1) Solution required for MOF functional layer preparation
[0324] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water were mixed in molar ratios of 50:1:1:0.0005, 100:1:1:0.001, 200:1:1:0.002, 500:1:1:0.005, and 1000:1:1:0.001 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0325] (2) Base film pretreatment
[0326] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0327] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0328] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain the separation membrane.
[0329] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0330] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0331] The separation membranes prepared in Examples 25-29 were tested for separation coefficients and membrane fluxes of hexane and nitrogen. The membrane performance test data are shown in Table 7.
[0332] Table 7
[0333]
[0334] As shown in Table 7, with the decrease in the proportion of monomer content in the formulation (lower concentration), the nitrogen / n-hexane separation coefficient of the prepared separation membrane showed an increasing trend, rising from 34 to 51. The nitrogen flux also increased slightly, from 1.5 × 10⁻⁶. -6 mol / (m 2 The value of ·s·Pa rose to nearly 3×10 -6 mol / (m 2 This is mainly because as the monomer concentration decreases, the in-situ polymerization reaction becomes more ordered, resulting in a denser functional layer structure with fewer defects and higher crystallinity, which is beneficial for improving the separation coefficient. At higher monomer concentrations, due to the fast reaction rate and high ligand concentration, oligomers and agglomeration are easily formed, resulting in a loose crystal structure but with oligomers clogging the channels, leading to a decrease in both the separation coefficient and throughput. However, in Example 29, with a ratio of 1000:1:1:0.01, the separation coefficient drops sharply to less than 10, while the throughput exceeds 10 × 10⁻⁶. -6 mol / (m 2 (·s·Pa). This indicates that when the monomer concentration is too low, the functional layer of MOFs will have more defects, the flux will increase significantly, and the separation performance of the membrane cannot be maintained for a long time.
[0335]
Examples 30-37
[0336] (1) Solution required for MOF functional layer preparation
[0337] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 500:1:1:0.005 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0338] (2) Base film pretreatment
[0339] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0340] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0341] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and in-situ growth reaction is carried out at 120°C for 6h, 12h, 18h, 24h, 30h, 36h, 42h, and 48h to obtain the separation membrane.
[0342] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0343] (5) Clean the separation membrane described in step (4) to obtain the MOF organic gas separation membrane.
[0344] The separation membranes prepared in Examples 30-37 were tested for separation coefficients and membrane fluxes of hexane and nitrogen. The membrane performance test data are shown in Table 8.
[0345] Table 8
[0346]
[0347] As shown in Table 8, when the in-situ growth time increased from 12 h to 24 h, the separation coefficient of the MOF separation membrane rapidly increased from 30 to 50. This indicates that the formation of the MOF functional layer enables the membrane to separate nitrogen / n-hexane. Simultaneously, the nitrogen permeation flux remains at 3.0 × 10⁻⁶. -6 mol / (m 2 The flux is above 1000 N·m·Pa. Because the functional layer is composed of UiO-66 with uniform pore size distribution and extremely high porosity, its lattice pore size is 0.6 nm, which is slightly smaller than the size of n-hexane molecules. Therefore, the functional layer blocks the passage of n-hexane molecules, while nitrogen molecules with a diameter of 3.4-3.6 nm can pass through the MOFs functional layer, resulting in a very high flux.
[0348] With further increases in in-situ growth time, the separation coefficient remained stable at 52, while the flux gradually decreased. After a reaction time of 48 hours, the flux dropped to less than 1.5 × 10⁻⁶. -6 mol / (m 2(·s·Pa). This indicates that a continuous and dense separation layer can be formed within 24 hours. Further increasing the reaction time will only increase the thickness of the functional layer, and may even cause some oligomers, monomers, and solvents to be encapsulated within the functional layer, clogging the membrane pores and leading to a decrease in permeation flux. Therefore, the optimal in-situ growth time is 18-24 hours. With a separation coefficient reaching 50, the nitrogen permeation flux exceeds 3.1 × 10⁻⁶. -6 mol / (m 2 The flux (·s·Pa) is 10-15 times that of current silicone rubber organic gas separation membranes and more than 30 times that of imported polyimide hydrogen separation membranes.
[0349]
Example 38
[0350] (1) Solution required for MOF functional layer preparation
[0351] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 400:1:1:0.01 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0352] (2) Base film pretreatment
[0353] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0354] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0355] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain the separation membrane.
[0356] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0357] (5) The MOFs organic gas separation membrane obtained in step (4) is mixed with a solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water to prepare a second mixture, wherein the molar ratio of N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water is 400:1:1:0.01, and the ratio of the membrane surface area to the solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water is 0.5 m². 2 / L.
[0358] (6) The second mixture obtained in step (5) is heated at 120°C for 12 hours to obtain a separation membrane.
[0359] (7) Clean the separation membrane described in step (6) to obtain the MOF organic gas separation membrane.
[0360] Performance test data for this membrane show that the nitrogen flux at 0.1 MPa can reach 3.120 × 10⁻⁶. -6 mol / (m 2 The flux of propylene gas is only 0.089 × 10⁻⁶ Pa·s, while the flux of propylene gas is only 0.089 × 10⁻⁶ Pa·s. -6 mol / (m 2 (·s·Pa), the nitrogen / propylene separation coefficient is 35.05.
[0361]
Example 39
[0362] (1) Solution required for MOF functional layer preparation
[0363] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 400:1:1:0.01 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0364] (2) Base film pretreatment
[0365] (a) A mixture of polyacrylic acid (1000 mg / L), partially hydrolyzed polyacrylic acid, and polyvinyl alcohol was mixed with zirconium tetrachloride at a molar ratio of 2:1 and stirred for 1 hour to obtain the reaction solution.
[0366] (b) After washing with water and ethanol and drying, the 500 nm pore size polypropylene hollow fiber base membrane was used to prepare a solution with a surface area of 1 m². 2 / L (i.e., coating a 1 square meter film with 1L of the solution generated in step (a)), coating the dried base film surface with the solution generated in (a), and then drying it to attach a certain amount of zirconium atoms to the base film surface.
[0367] (3) The ratio of the surface area of the pretreated base film to the solution described in (1) is 1m².2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the solution required for the preparation of the MOFs functional layer in step (1)), and is immersed in the solution required for the preparation of the MOFs functional layer to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain the separation membrane.
[0368] (4) Take out the separation membrane obtained in step (3) and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0369] (5) The MOFs organic gas separation membrane obtained in step (4) is mixed with a solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water to prepare a second mixture, wherein the molar ratio of N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water is 400:1:1:0.01, and the ratio of the membrane surface area to the solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride, and pure water is 0.5 m². 2 / L.
[0370] (6) The second mixture obtained in step (5) is heated at 120°C for 12 hours to obtain a separation membrane.
[0371] (7) Siloxane coating:
[0372] Room temperature hydroxysilane, tetraethyl orthosilicate, and n-hexane were mixed in a ratio of 1:0.2:8.8 and stirred at high speed for 24 hours to dissolve. 0.01% dibutyltin dilaurate was added, and the mixture was pre-crosslinked for 5 hours to obtain a silane coating solution with a viscosity of 100 mPa·s. Subsequently, the MOFs organic gas separation membrane prepared in step (6) was immersed in the silane coating solution, allowed to stand for 100 seconds, and then removed. The coating thickness was 5-10 micrometers.
[0373] (8) Thermal crosslinking: The coated organic gas separation membrane is thermally crosslinked at 80°C for 1 hour to finally obtain an organic gas separation membrane with a three-layer structure.
[0374] Performance test data for this membrane show that the nitrogen flux at 0.1 MPa can reach 1.086 × 10⁻⁶. -7 mol / (m 2 The flux of propylene gas was 0.03298 × 10⁻⁶ s·Pa, while the flux of propylene gas was 0.03298 × 10⁻⁶ s·Pa. -7 mol / (m 2 The nitrogen / propylene separation coefficient is 32.92 (·s·Pa).
[0375] Comparative Example 1
[0376] (1) Preparation of precursor solution
[0377] Dissolve 0.42 g zirconium chloride and 0.30 g terephthalic acid in 67.5 mL of N,N-dimethylformamide (DMF), and add 32 μL of deionized water. Stir and sonicate to fully dissolve the reagents, and transfer the clear precursor solution to a hydrothermal reactor.
[0378] (2) Heat treatment
[0379] Hollow fiber membranes made of polyvinylidene fluoride (PVDF) were vertically immersed in a prepared precursor solution using a fixing frame and heat-treated at a constant temperature of 120°C for 72 hours. During the heat treatment, the hollow fiber membranes dissolved entirely in the precursor solution, preventing further preparation of the separation membrane.
[0380] The condition of the base film and solution after the reaction is as follows: Figure 6 As shown.
[0381] Comparative Example 2
[0382] (1) Precursor solution required for MOF functional layer preparation
[0383] Same as Example 1.
[0384] (2) Base film pretreatment
[0385] (a) Same as Example 1;
[0386] (b) A polyvinylidene fluoride (PVDF) membrane with a pore size of 500 nm was used, and the rest was the same as in Example 1. The membrane was heat-treated at a constant temperature of 120°C for 72 hours. During the heat treatment, the hollow fiber membrane dissolved in the precursor solution, preventing further preparation of the separation membrane.
[0387] The condition of the base film and solution after the reaction is as follows: Figure 7 As shown.
[0388] Comparative Example 3
[0389] (1) Preparation of precursor solution
[0390] Dissolve 0.42 g zirconium chloride and 0.30 g terephthalic acid in 67.5 mL of N,N-dimethylformamide (DMF), and add 32 μL of deionized water. Stir and sonicate to fully dissolve the reagents, and transfer the clear precursor solution to a hydrothermal reactor.
[0391] (2) Heat treatment
[0392] A 500 nm pore size polypropylene hollow fiber base membrane was vertically immersed in the prepared precursor solution using a fixture and heat-treated at a constant temperature of 120 °C for 72 h. After the heat treatment was completed, it was naturally cooled.
[0393] (3) Ultrasonic treatment
[0394] The obtained membrane was removed and ultrasonically treated for 5 seconds to remove particles with poor adhesion, thus obtaining a substrate with seed crystals.
[0395] (4) Formation of a continuous membrane
[0396] The substrate with seed crystals deposited was heat-treated twice in the same manner as (2) to obtain a continuous film. The film was first cleaned with DMF and then with methanol and dried at room temperature.
[0397] The electron microscope images of the prepared film surface are as follows: Figure 8 ,from Figure 8 As can be seen, the octahedral structures in the MOF functional layers of the prepared membrane exist independently and do not form an inter-embedded structure.
[0398] Comparative Example 4
[0399] (1) Solution required for MOF functional layer preparation
[0400] N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in a molar ratio of 400:1:1:0.01 and stirred thoroughly to obtain the solution required for the preparation of MOF functional layers.
[0401] (2) A 500 nm pore size polypropylene hollow fiber base membrane is prepared according to a ratio of the base membrane surface area to the solution described in (1) of 1 m². 2 / L (i.e., a membrane with a surface area of 1 square meter is placed in 1L of the MOFs preparation solution described in step (1)), and is immersed in the MOFs preparation solution to obtain the first mixture. Nitrogen gas is introduced for protection, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain the separation membrane.
[0402] (3) Take out the separation membrane obtained in step (2), and clean the unreacted monomers and solvents on the membrane surface to obtain the MOF organic gas separation membrane.
[0403] (4) Clean the separation membrane described in step (3) to obtain the MOF organic gas separation membrane.
[0404] The electron microscope images of the prepared film surface are as follows: Figure 9 ,from Figure 9 As can be seen, without base film pretreatment, the base film has some discontinuous crystals attached. The crystals are composed of multiple octahedrons aggregated together, without forming a continuous structure.
[0405] Any limitations of this invention have been described with reference to exemplary embodiments, but it should be understood that the terms used herein are descriptive and explanatory, not limiting. Modifications and revisions can be made to this invention within the scope of the claims as specified herein, without departing from the scope and spirit of the invention. Although the invention described herein relates to specific methods, materials, and embodiments, it does not imply that the invention is limited to the specific examples disclosed herein; rather, the invention is extendable to all other methods and applications having the same functionality.
Claims
1. A metal-organic framework (MOF) separation membrane, comprising a base membrane and a MOF functional layer, wherein the MOF functional layer comprises one or more interlocking polyhedral structures; the polyhedrons are constructed from multiple lattices; the lattices are composed of metal atoms and organic ligands; the metal atoms are selected from zirconium atoms, niobium atoms, molybdenum atoms, or cobalt atoms; the organic ligands are selected from terephthalic acid and / or nitroterephthalic acid; The inter-embedded polyhedral structure refers to a part of the structure of a polyhedron being inserted into the interior of other polyhedral structures that are adjacent or close to it, or a polyhedron sharing a portion of its lattice with one or more surrounding polyhedra. The method for preparing the separation membrane includes the following steps: (1) Prepare a solution comprising a first organic solvent, an organic ligand, a first metal compound and an auxiliary agent, wherein the auxiliary agent is selected from water or glacial acetic acid; (2) Pre-treat the base film by introducing metal atoms from the first metal compound in step (1) onto its surface; (3) The base membrane after pretreatment in step (2) is mixed with the solution in step (1) to obtain a first mixture. The first mixture is heated to react and a metal-organic framework material separation membrane is obtained. (4) Optionally, the separation membrane is cleaned; The first organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, and dimethylacetamide; The organic ligand is selected from terephthalic acid and / or nitroterephthalic acid; The first metal compound is selected from one or more of zirconium compounds, niobium compounds, molybdenum compounds, and cobalt compounds; Step (2) includes the following steps: (2A-1) Prepare a solution containing polyacrylic acid, polyvinyl alcohol, and a second metal compound. (2A-2) Coat the solution from step (2A-1) onto the base film; The metal atoms in the second metal compound are the same as those in the first metal compound in step (1); Alternatively, step (2) may include the following steps: (2B-1) Prepare a solution comprising the metal complex shown in Formula I and a second organic solvent. (2B-2) Mix the base film with the solution from step (2B-1). (2B-3) The base film after mixing in step (2B-2) is cleaned with the third solvent; Formula I In Formula I, Q is selected from amide, carbonyl or C1-C6 alkylene; R1 is selected from hydrogen, C1-C6 alkyl, C1-C6 alkoxy or halogen; M1 is the same as the metal atom in the first metal compound in step (1); m is 5-20; n is 1-10; Alternatively, step (2) may include the following steps: (2C-1) Prepare a solution containing the metal complex shown in Formula II. (2C-2) The base film is mixed with the solution from step (2C-1) to obtain a mixture, and the mixture is subjected to a polymerization reaction under microwave irradiation conditions; Formula II In Formula II, X is selected from amide, carbonyl or C1-C6 alkylene groups; R2, R3 and R4 are the same or different, and are each independently selected from hydrogen, C1-C6 alkyl, C1-C6 alkoxy or halogen; M2 is the same as the metal atom in the first metal compound in step (1).
2. The separation membrane according to claim 1, characterized in that, At least 20% of the polyhedra in the functional layer of the metal-organic framework material are interlocked; and / or The average pore size of the metal-organic framework metal material functional layer is 0.1-2.0 nm; and / or The thickness of the functional layer of the metal-organic framework material is 200-5000 nm; and / or The base film is selected from one or more of polypropylene film, polyethylene film, polyvinyl chloride film, or polytetrafluoroethylene film; and / or The pore size of the base film is 10-10000 nm.
3. The separation membrane according to claim 1, characterized in that, In the interlocking polyhedral structure, two adjacent polyhedra share a lattice and / or the distance between the centers of two adjacent polyhedra is less than the average length L of the two adjacent polyhedra.
4. The separation membrane according to claim 1, characterized in that, In the inter-embedded polyhedral structure, two adjacent polyhedra share a common lattice and / or the distance between the centers of two adjacent polyhedra is less than 0.95L.
5. The separation membrane according to claim 1, characterized in that, In the inter-embedded polyhedral structure, two adjacent polyhedra share a common lattice and / or the distance between the centers of two adjacent polyhedra is 0.2-0.9L.
6. The separation membrane according to claim 1, characterized in that, At least 30% of the polyhedra in the functional layer of the metal-organic framework material are interlocked; and / or The average pore size of the metal-organic framework metal material functional layer is 0.30-0.96 nm; and / or The thickness of the functional layer of the metal-organic framework material is 1000-5000 nm; and / or The pore size of the base film is 50-5000 nm.
7. The separation membrane according to claim 6, characterized in that, At least 40% of the polyhedra in the functional layer of the metal-organic framework material are interlocked; and / or The pore size of the base film is 200-1000 nm.
8. The separation membrane according to claim 6, characterized in that, At least 50% of the polyhedra in the functional layer of the metal-organic framework material are inter-embedded.
9. The separation membrane according to claim 6, characterized in that, At least 60% of the polyhedra in the functional layer of the metal-organic framework material are inter-embedded.
10. The separation membrane according to claim 6, characterized in that, At least 80% of the polyhedra in the functional layer of the metal-organic framework material are inter-embedded.
11. The separation membrane according to claim 1, characterized in that, The polyhedron includes hexahedrons and / or octahedrons.
12. The separation membrane according to claim 11, characterized in that, The length of the polyhedron is 50-2000 nm.
13. The separation membrane according to claim 11, characterized in that, The length of the hexahedron is 50-1000 nm, of which the proportion of hexahedrons with a length of 400-600 nm is 50-80%.
14. The separation membrane according to claim 11, characterized in that, The length of the octahedron is 200-2000 nm, of which octahedrons with a length of 800-1200 nm account for 60-80%.
15. The separation membrane according to claim 11, characterized in that, Each of the octahedrons or hexahedrons is constructed from multiple lattices formed by zirconium metal atoms and terephthalic acid.
16. The separation membrane according to any one of claims 1-15, characterized in that, The metal-organic framework material functional layer further includes an auxiliary functional layer; the auxiliary functional layer is a portion used to repair areas where the embedded octahedral or embedded hexahedral structures may not be fully formed; and / or The separation membrane also includes an organosilicon layer located on the surface of the functional layer of the metal-organic framework material.
17. The separation membrane according to claim 1, characterized in that, In step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (10-1000):(1-100):(1-100), and / or the molar ratio of the first organic solvent and the auxiliary agent water is 100:(0.001-0.05) or the molar ratio of the first organic solvent and the auxiliary agent glacial acetic acid is 100:(20-60).
18. The separation membrane according to claim 17, characterized in that, In step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (100-1000):(1-10):(1-10).
19. The separation membrane according to claim 17, characterized in that, In step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (100-700):1:
1.
20. The separation membrane according to claim 17, characterized in that, In step (1), the molar ratio of the first organic solvent, the organic ligand and the first metal compound is (400-600):1:
1.
21. The separation membrane according to claim 1, characterized in that, In step (2A-1), the polyacrylic acid comprises polyacrylic acid and partially hydrolyzed polyacrylic acid, and / or the mass concentration of polyacrylic acid and polyvinyl alcohol in the solution is 500-2000 mg / L, and the molar ratio of the total of the polyacrylic acid and polyvinyl alcohol to the metal compound is 1-3:1; and / or In step (2A-1), the second metal compound is selected from one or more of zirconium compounds, niobium compounds, molybdenum compounds, and cobalt compounds; and / or In step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 0.1-10 m². 2 / L.
22. The separation membrane according to claim 21, characterized in that, The second metal compound is zirconium tetrachloride; and / or In step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 0.5-5 m². 2 / L.
23. The separation membrane according to claim 21, characterized in that, In step (2A-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2A-1) is 1-2 m². 2 / L.
24. The separation membrane according to claim 1, characterized in that, In step (2B-1), in formula I, M1 is selected from zirconium, niobium, molybdenum, or cobalt atoms; and / or, Q is selected from an amide group, and R1 is selected from a C3-C6 alkyl group; and / or In step (2B-1), the second organic solvent is selected from one or more organic solvents capable of causing the base film to swell; the third solvent is selected from one or more solvents capable of deswelling the swollen base film; and / or In the solution of step (2B-1), the mass concentration of the metal complex represented by formula I is 500-2000 mg / L; and / or In step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 0.1-10 m². 2 / L.
25. The separation membrane according to claim 24, characterized in that, In step (2B-1), the second organic solvent is selected from one or more of C5-C10 aliphatic hydrocarbons, C1-C10 halogenated aliphatic hydrocarbons, C6-C20 aromatic hydrocarbons, and C6-C20 halogenated aromatic hydrocarbons; and / or In step (2B-1), the third solvent is selected from water; and / or In step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 0.5-5 m². 2 / L.
26. The separation membrane according to claim 25, characterized in that, In step (2B-1), the second organic solvent is selected from one or more of n-pentane, n-hexane, chloroform, carbon tetrachloride, benzene, and toluene; and / or In step (2B-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2B-1) is 1-2 m². 2 / L.
27. The separation membrane according to claim 1, characterized in that, In step (2C-1), in formula II, M2 is selected from zirconium, niobium, molybdenum, or cobalt atoms; and / or, X is selected from an amide group; R2, R3, and R4 may be the same or different, and each is independently selected from hydrogen, C1-C3 alkyl groups; and / or In step (2C-1), the solution of the metal complex is an aqueous solution of the metal complex, and / or the mass concentration of the metal complex shown in Formula II is 500-20000 mg / L; and / or In step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 0.1-10 m². 2 / L; and / or In step (2C-2), the microwave intensity of the microwave radiation is 500-2000 μw / cm. 2 The frequency is 1000-200000Hz.
28. The separation membrane according to claim 27, characterized in that, In step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 0.5-5 m². 2 / L.
29. The separation membrane according to claim 28, characterized in that, In step (2C-2), the ratio of the surface area of the base film to the volume of the solution obtained in step (2C-1) is 1-2 m². 2 / L.
30. The separation membrane according to claim 1, characterized in that, In step (3), the ratio of the surface area of the pretreated base film in step (2) to the volume of the solution obtained in step (1) is (0.01-100) m². 2 / L; and / or In step (3), the reaction temperature is 50-300℃; and / or In step (3), the reaction pressure is 0.01-0.5 MPa; and / or In step (3), the reaction time is 1-100h.
31. The separation membrane according to claim 30, characterized in that, In step (3), the ratio of the surface area of the base film after pretreatment in step (2) to the volume of the solution obtained in step (1) is (0.01-10) m². 2 / L; and / or In step (3), the reaction temperature is 100-200℃; and / or In step (3), the reaction pressure is 0.05-0.1 MPa; and / or In step (3), the reaction time is 10-72 h.
32. The separation membrane according to claim 31, characterized in that, In step (3), the ratio of the surface area of the base film after pretreatment in step (2) to the volume of the solution obtained in step (1) is 0.5-2 m². 2 / L; and / or In step (3), the reaction time is 15-30 hours.
33. The separation membrane according to any one of claims 17-32, characterized in that, The method further includes the following steps: (5) Perform one or more repair treatments on the metal-organic framework material separation membrane obtained in step (3) or (4).
34. The separation membrane according to claim 33, characterized in that, The repair process includes the following steps: (A) A metal-organic framework material separation membrane is mixed with a solution containing a first organic solvent, an organic ligand, a first metal compound, and an additive to obtain a second mixture, wherein the additive is selected from water or glacial acetic acid; (B) The second mixture is heated to allow a reaction to occur, thereby obtaining a metal-organic framework separation membrane; (C) Optionally, the separation membrane is cleaned.
35. The separation membrane according to claim 34, characterized in that, In step (A), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (10-1000):(1-100):(1-100); and / or, the molar ratio of the first organic solvent and the auxiliary agent water is 100:(0.001-0.05) or the molar ratio of the first organic solvent and the auxiliary agent glacial acetic acid is 100:(20-60); and / or The reaction temperature in step (B) is 50-300℃, the reaction pressure is 0.01-0.5MPa, and the reaction time is 1-100h.
36. The separation membrane according to claim 35, characterized in that, In step (A), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (100-1000):(1-10):(1-10); and / or The reaction time in step (B) is 5-50 hours.
37. The separation membrane according to claim 36, characterized in that, In step (A), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (100-700):1:1; and / or The reaction time in step (B) is 10-20 hours.
38. The separation membrane according to any one of claims 34-37, characterized in that, The method further includes the following steps: coating the surface of the metal-organic framework material separation membrane obtained in step (3) or (4) or (B) or (C) with silane coating liquid, heating the metal-organic framework material separation membrane coated with silane coating liquid to cause the silane coating liquid to undergo a crosslinking reaction, thereby obtaining a metal-organic framework material separation membrane including an organosilicon layer.
39. The separation membrane according to claim 38, characterized in that, The cross-linking reaction is carried out at a temperature of 50-300℃ for a time of 0.1-20h.
40. The separation membrane according to claim 38, characterized in that, The preparation of the silane coating solution includes the following steps: S1, mix and dissolve silane, crosslinking agent and organic solvent to obtain a mixture; S2, a catalyst is added to the mixture to allow it to undergo pre-crosslinking, resulting in a silane coating solution.
41. The separation membrane according to claim 40, characterized in that, In step S1, the ratio of silane, crosslinking agent, and organic solvent is (0.1-10):(0.1-10):(90-100); and / or In step S1, the silane is a monomer of a siloxane material, including one or more of dimethylsiloxane, cured silicone rubber, and vulcanized silicone rubber mixed in any proportion; and / or, the crosslinking agent includes tetraethyl orthosilicate or tetramethoxysilane; and / or, the organic solvent includes at least one of heptane, pentane, toluene, benzene, xylene, and hexane; and / or In step S2, the catalyst is an organotin catalyst or a titanium complex catalyst; the amount of catalyst used is 0.01-1 wt%; and / or, the pre-crosslinking time in step S2 is 1-48 h; and / or, the viscosity of the silane coating solution is 100-50000 mPa·s.
42. The separation membrane according to claim 41, characterized in that, In step S1, the ratio of silane, crosslinking agent, and organic solvent is (1-10):(1-10):(90-100); and / or In step S1, the organic solvent is n-hexane; and / or In step S2, the amount of catalyst used is 0.01-0.1 wt%; and / or, the pre-crosslinking time in step S2 is 10-30 h; and / or, the viscosity of the silane coating solution is 100-5000 mPa·s.
43. The separation membrane according to claim 42, characterized in that, In step S1, the ratio of silane, crosslinking agent, and organic solvent is 9:1:90; and / or The pre-crosslinking time in step S2 is 24 hours; and / or the viscosity of the silane coating liquid is 2000 mPa·s.
44. The separation membrane according to any one of claims 39-43, characterized in that, The method further includes the following steps: the prepared metal-organic framework material separation membrane is treated by adding it to an alkaline solution to control its pore size.
45. The separation membrane according to claim 44, characterized in that, The alkaline solution is a sodium hydroxide solution with a pH of 9-13; the addition process is accompanied by stirring, the flow rate obtained by stirring is 0.01-1 m / s; the stirring time is 10-120 min.
46. The separation membrane according to claim 45, characterized in that, The flow rate obtained by stirring during the addition process is 0.1 m / s; and / or the stirring time is 30-60 min.
47. The application of the metal-organic framework material separation membrane according to any one of claims 1-46 in the separation of organic matter.
Citation Information
Patent Citations
Preparation method of metal organic framework ZIF-8 (zero insert force-9) film
CN102794115A
Preparation method of high dispersion metal-organic framework (MOF) / organic hybrid priority alcohol through composite membrane
CN104001426A
Method for improving the gas separation performance of supported MOF membrane by utilizing polymer coating
CN108939958A
Method for separating solvent mixed liquor, and metal organic structure separation membrane used therefor
JP2017202449A
